Efektivitas Media Stik Angka untuk Meningkatkan Kemampuan Penjumlahan pada Siswa Disabilitas Intelektual Ringan (Single Subject Research Fase D Kelas VIII di SLB Negeri 2 Padang) - Hasanah, Fifi Latifah Nur; Irdamurni, Irdamurni (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to improve the ability to add downward series with the storage technique using Number Stick Media. The researcher used quantitative research type with experimental approach in the form of Single Subject Research (SSR) with A-B-A design. Techniques in data collection in the form of tests and data collection tools for test questions. The data produced is analyzed using visual graphic analysis. The subjects of this study were students with Mild Intellectual Disabilities Phase D class VIII SLB Negeri 2 Padang City. The results of the study showed that in the baseline condition (A1) which was conducted three times with observations and obtained a stable percentage of 27%. In the Intervention condition (B) which was conducted seven times with observations and obtained a stable percentage of 90% and in the baseline condition (A2) which was conducted three times with observations and obtained a stable percentage of 90%. Based on the results of the study, it can be concluded that the number stick learning media can improve the ability to add downward series with the storage technique for children with Mild Intellectual Disabilities